Analisis Permasalahan Pengelolaan Zakat Di Masa New Normal Pada Dompet Dhuafa Waspada Medan - Halimah Tusadiyah; Sarwo Edi; Asmaul Husna; Fauziah Hanum (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2023)
This research study was conducted on zakat receipts which have been greatly facilitated by online zakat payments both from applications and from e-commerce platforms that already offer zakat payment features in e-commerce (Hasanah, 2021). In assisting in maximizing the management of zakat funds in the new normal, the researchers limit this research by focusing on the analysis of problems in zakat management carried out by Dompet Dhuafa Waspada Medan in the new normal period. This study aims to determine how the problems of zakat management in the new normal period in Dompet Dhuafa Waspada Medan.